New Directions in the Ethics and Politics of Speech - Messina, J.P (Political Philosophy for the Real World, 2023)
This book features new perspectives on the ethics and politics of free speech. Contributors draw on insights from philosophy, psychology, political theory, journalism, literature, and history to respond to pressing problems involving free speech in liberal societies. Recent years have seen an explosion of academic interest in free speech. However, most recent work has focused on constitutional protections for free speech and on issues related to academic freedom and campus politics. The chapters in this volume set their sights more broadly on the non-state problems that we collectively face in attempting to realize a healthy environment for free discourse. The volume's contributors share the assumption that threats to free speech do not come exclusively from state sources or bad actors, but from ordinary strategic situations in which all may be acting in good faith. Contributors take seriously the idea that our current cultural moment provides plenty of reason to be concerned about our intellectual climate and offer new insights for how to make things better.　 New Directions in the Ethics and Politics of Speech will be of interest to researchers and students working in ethics, political philosophy, social theory, and law.